Graphene oxide nanosheets modulate spinal glutamatergic transmission and modify locomotor behaviour in an in vivo zebrafish model. Issue 8 (19th June 2020) - Cellot, Giada; Vranic, Sandra; Shin, Yuyoung; Worsley, Robyn; Rodrigues, Artur Filipe; Bussy, Cyrill; Casiraghi, Cinzia; Kostarelos, Kostas; McDearmid, Jonathan Robert
Abstract : The article reports that graphene oxide nanosheets (s-GO), by interfering with synapses, have the potential to be used as behavioural modulators. Abstract : Graphene oxide (GO), an oxidised form of graphene, is widely used for biomedical applications, due to its dispersibility in water and simple surface chemistry tunability. In particular, small (less than 500 nm in lateral dimension) and thin (1–3 carbon monolayers) graphene oxide nanosheets (s-GO) have been shown to selectively inhibit glutamatergic transmission in neuronal cultures in vitro and in brain explants obtained from animals injected with the nanomaterial. This raises the exciting prospect that s-GO can be developed as a platform for novel nervous system therapeutics. It has not yet been investigated whether the interference of the nanomaterial with neurotransmission may have a downstream outcome in modulation of behaviour depending specifically on the activation of those synapses. To address this problem we use early stage zebrafish as an in vivo model to study the impact of s-GO on nervous system function. Microinjection of s-GO into the embryonic zebrafish spinal cord selectively reduces the excitatory synaptic transmission of the spinal network, monitored in vivo through patch clamp recordings, without affecting spinal cell survival. This effect is accompanied by a perturbation in the swimming activity of larvae, which is the locomotor behaviour generated by the neuronal network of the spinal cord. Such results indicate that the impact of s-GO on glutamate based neuronal transmission is preserved in vivo and can induce changes in animal behaviour. These findings pave the way for use of s-GO as a modulator of nervous system function.